2009
DOI: 10.2967/jnumed.108.061507
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Trigger PSA and PSA Kinetics on 11C-Choline PET/CT Detection Rate in Patients with Biochemical Relapse After Radical Prostatectomy

Abstract: The purpose of this study was to investigate the effect of total prostate-specific antigen (PSA) at the time of 11 C-choline PET/ CT (trigger PSA), PSA velocity (PSAvel), and PSA doubling time (PSAdt) on 11 C-choline PET/CT detection rate in patients treated with radical prostatectomy for prostate cancer, who showed biochemical failure during follow-up. Methods: A total of 190 patients treated with radical prostatectomy for prostate cancer who showed an increase in PSA (mean, 4.2; median, 2.1; range, 0.2-25.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
1
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(132 citation statements)
references
References 37 publications
6
108
1
17
Order By: Relevance
“…Thus, if 68 Ga-PSMA ligand PET/CT were used in that preselected setting, the detection rate would potentially be different. Similarly to choline derivates, our results state a higher detection rate in patients with a higher PSAvel, albeit the P value of 0.0532 could be designed as borderline from a purist statistical point of view (3,32,35). Nevertheless, 68 Ga-PSMA ligand PET/CT offers a high rate of positive findings also in patients with low changes in PSA kinetics, with a detection rate of 81.8% compared with 12% for 11 C-choline at a PSAvel of 1 ng/mL/Y (35).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Thus, if 68 Ga-PSMA ligand PET/CT were used in that preselected setting, the detection rate would potentially be different. Similarly to choline derivates, our results state a higher detection rate in patients with a higher PSAvel, albeit the P value of 0.0532 could be designed as borderline from a purist statistical point of view (3,32,35). Nevertheless, 68 Ga-PSMA ligand PET/CT offers a high rate of positive findings also in patients with low changes in PSA kinetics, with a detection rate of 81.8% compared with 12% for 11 C-choline at a PSAvel of 1 ng/mL/Y (35).…”
Section: Discussionmentioning
confidence: 78%
“…Similarly to choline derivates, our results state a higher detection rate in patients with a higher PSAvel, albeit the P value of 0.0532 could be designed as borderline from a purist statistical point of view (3,32,35). Nevertheless, 68 Ga-PSMA ligand PET/CT offers a high rate of positive findings also in patients with low changes in PSA kinetics, with a detection rate of 81.8% compared with 12% for 11 C-choline at a PSAvel of 1 ng/mL/Y (35). Notably, our data show no clear trend toward higher detection rates with a decreasing PSAdt, compared with reports for 11 C-and 18 F-choline (32,35).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Even though the exact role of the examination is still being discussed it seems that CH-PET/CT starts playing a role in the management of patients with a biochemical relapse [10] [11]. Several studies have demonstrated that CH-PET/CT either labeled with C-11 [12] [13] or with F-18 [14] [15] can detect tumor recurrence at PSA levels of above 2ng/ml giving the clinicians the opportunity of a curative intended salvage procedure at an early time-point of the recurrence [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Rinnab reported that 11 C-choline PET/CT had a sensitivity of 89% and specificity of 40% for patients with post-RP PSA levels <2.5 ng/mL (50). Castelluci reported that PSA level, PSA velocity and PSA doubling time were predictive factors for the outcome of 11 C-choline PET/CT for patients with post-RP PSA relapse (51). Scattoni, in a series of 21 patients with post-RP PSA relapse (median PSA: 1.98 ng/mL), correlated the outcome of 11 C-choline PET/CT for the detection of lymph node metastases with pelvic +/-retroperitoneal lymph node dissection (52).…”
mentioning
confidence: 99%